Dialogo con Cicerone - Albrecht, Michael von (Prometheus, 2021)
An Italian translation of Michael von Albrecht’s poem Cicero ad colloquium evocatus. The translator, in agreement with the author, has chosen blank verse (hendecasyllables) ‒ the meter of epic poetry in Italian, and traditionally used to translate poems in hexameters.